Novel extracellular products of Mycobacterium tuberculosis: composition, synthesis, and relevance to disease - Obregón-Henao, Andrés, author; Belisle, John T., advisor; Brennan, Patrick J., committee member; Curthoys, Norman P., committee member; Dow, Steven W., committee member (Colorado State University. Libraries, 2013)
Mycobacterium tuberculosis (Mtb) is a bacterium causing great morbidity and mortality especially in developing countries. In order to identify possible areas of intervention to positively alter the history of the disease, a better identification and characterization of Mtb virulence determinants is required. Specifically, biosynthetic routes for these virulence determinants should be pursued. Furthermore, the interaction between the host and Mtb virulence determinants should be characterized at a molecular level. It is hoped that unraveling these pathogenesis mechanisms could lead to novel strategies to combat the infection. In Chapter II, the identification of secreted Mtb molecules that induce macrophage apoptosis was performed. Apoptosis is a mechanism of host cell death and in the life cycle of Mtb, different modalities of host cell death have been suggested to tip the balance between bacterial eradication and multiplication. However, a systematic approach to identify and characterize secreted Mtb molecules that modulate host cell death, has not been performed. Surprisingly, extracellular Mtb RNA fragments were identified as a potent inducer of host cell apoptosis. This extracellular RNA was identified as predominantly rRNA and tRNA fragments that accumulated early during in vitro culture of Mtb. Mechanistic studies determined that the Mtb RNA induced macrophage apoptosis through a caspase-8-dependent, TNF-α-independent mechanism. Importantly, Mtb RNA abrogated the macrophage's ability to control an Mtb infection. In Chapter II, the first description of an extracellular Mtb RNA with potent biological activity was performed. This opens an exciting field in research of host interactions with pathogen nucleic acids. Chapters III and IV were devoted to identifying the biochemical pathway involved in α-L-polyGlutamine (α-L-polyGln) biosynthesis and determining its role in pathogenesis in the murine model of TB. α-L-polyGln is an Mtband Mycobacterium bovis (M. bovis) specific product and its presence in virulent Mycobacterium spp., suggest that it could play an important role in pathogenesis. Bacillus anthracis (B. anthracis) synthesizes γ-D-polyGlutamate (γ-D-polyGlu), an amino acid polymer that is present in its capsule and is absolutely required for pathogenicity. As the pathway for B. anthracis γ-D-polyGlu biosynthesis has been well characterized, it was used as a model to start elucidating the Mtb α-L-polyGln biosynthetic pathway. Bioinformatics analysis suggested that Rv0574c and Rv2394 are the Mtb homologues for B. anthracis CapA and CapD, respectively. In Chapter III, a complete biochemical characterization of Rv2394 was performed. Similar to other γ-glutamyltranspeptidases (GGTs), Rv2394 had a conserved catalytic motif consisting of a Threonine (Thr) residue. Mutating this Thr residue to Alanine (Ala) abrogated the enzymatic activity of Rv2394, including its autocatalytic activation. In contrast to eukaryote GGT, Rv2394 was able to perform a GGT activity in the presence of physiological relevant acceptors such as di- or oligopeptides containing Glutamate (Glu) or Glutamine (Gln). In addition to its autocatalytic activation, Rv2394 was shown to be post-translationally modified with hexose residues. A putative phosphorylation and acylation modification also seemed to be present in Rv2394. In Chapter IV, Mtb mutants for rv0574c and rv2394 were engineered and characterized biochemically to determine if the concentration of α-L-polyGln had been altered. Furthermore, the mutant's virulence was evaluated in the murine model of TB. Consistent with a putative role in α-L-polyGln, both mutants had reduced concentrations of Glu and ammonia in the cell wall. Furthermore, preliminary analysis suggested that the apolar lipid profiles were also altered by these mutations. In the murine model, Mtb mutants had a tendency to grow faster in the initial stages of disease. However, the difference between wild type (WT) and mutant strains was not statistically significant and normalized during the later stages of disease. Furthermore, mutant Mtb also seemed to induce more lung damage. In contrast to bacterial burden, this difference persisted throughout the course of the study. Altogether, these results suggest that Rv0574c and Rv2394 participate in the biosynthesis of α-L-polyGln. Remarkably, similar biochemical and phenotypic results were obtained for both mutants despite being encoded in different loci. These initial results provide the foundation for future studies characterizing the biochemical pathway involved in α-L-polyGln biosynthesis.
Keywords: latency; poly-glutamine; secretion; transpeptidase; tuberculosis; RNA